PERANAN BIMBINGAN PENYULUHAN ISLAM DALAM PEMBENTUKAN KARAKTER ANAK DI TAMAN PENDIDIKAN ALQUR’AN - Fadhil Hardiansyah; Reni Oktaviani; Dinny Rahmayanty (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Islamic counseling guidance is an effort to provide assistance in the form of directions delivered by someone who is more knowledgeable in his field, so that someone can optimize himself well. This study aims to determine the role of Islamic counseling guidance in the formation of children's character in the Al-Qur'an Education Park. This type of research is field research, with the nature of qualitative descriptive research. This study uses interview data collection techniques, observation and documentation. Interviews were conducted with ustadzahs, children, and parents of children who recited the Koran at the Al-Qur'an Education Park. All the data were analyzed deductively. This type of research is field research, with the nature of qualitative descriptive research. This study uses interview data collection techniques, observation and documentation. Based on the results of research on the role of Islamic counseling guidance in the formation of children's character in the Al-Qur'an Education Park, there are Islamic counseling activities in the Al-Qur'an Education Park, one of which is in the form of delivering material. As for the delivery of material related to character, namely commendable and despicable moral material. Likewise, at the beginning of the character of the children who recited the Koran at the Al-Qur'an Education Park, there were children who had negative characters such as being lazy, temperamental, and speaking harshly. Punishment and motivation. Apart from that, in the Al-Qur'an Education Park the ustadzah instill values such as religious and discipline to children who recite the Koran in the Al-Qur'an Education Park which can change the character of children from negative ones to better ones. Activities related to Islamic counseling guidance in the Al-Qur'an Education Park are recitation of the Qur'an, Arabic such as memorizing vocabulary, then short letters, prayer, gymnastics, natural meditation and delivery of material such as monotheism, fiqh, tajwid, reading and writing the Qur'an and morals. Activities related to Islamic extension guidance in the Al-Qur'an Education Park in strengthening character are the delivery of moral material (commendable and despicable). Handling for children who have both positive and negative characters such as exemplary, habituation, advice and punishment. Planting related to character building values such as responsibility, healthy, clean, religious, and discipline.